A cognitive approach to the allegedly left-headed prefix verbs in German: : Arguments for the interaction of prefixation and event-schema metonymy - Baeskow, Heike (Linguistik Online, 2023)
In this article, the much discussed problem of apparently left-headed German prefix verbs (e. g. besohlen ‘sole’, erschneidern ‘obtain by tailoring’, verschimmeln ‘become mouldy’) will be addressed from a cognitive perspective. It will be argued that nominal bases are metonymically reconceptualized as events inside the derivatives. This proposal has two advantages over previous approaches. First, it is not necessary to assign verbal or verbalizing properties to the prefixes be-, ent-, er-, ver-, and zer-, which have their origin in prepositions or adverbs. Secondly, an overgeneration of virtual verbs, i. e. of verbs which are not or no longer attested (e. g. *dachen ‘roof’, †sohlen ‘sole’) is avoided because the metonymic and hence purely conceptual verbalization process takes place in the context of the inseparable prefixes. The prefixes neither change the word-class of their bases nor provide argument structures, which are predicted by a small set of conceptual event schemata. The function of the prefixes is rather to add semantic or aspectual information. Synchronic support for the proposal to be presented first of all comes from the fact that conversion, which historically preceded prefixation in German, is still active. Contrastive analyses of English and German non-derived denominal verbs will illustrate this point. Moreover, many prefix verbs still co-exist with non-derived denominal verbs (e. g. schottern (< Schotter ‘gravel, ballast’) vs. beschottern, entschottern, verschottern). A more general observation is that the compatibility of denominal verbs with the holistic (or ‘synoptic’) perspective conveyed by the inseparable prefixes depends on the metonymic patterns underlying these verbs.